Maurice Echeverría’s Labios: A Disenchanted Story about Lesbians in Guatemala’s Postwar Reality - Yajaira M. Padilla (Studies in 20th & 21st Century Literature, 2013)
In the last two decades, lesbian, gay, and queer literary studies have gained significant ground in the broader field of Latin American cultural studies. Within this growing body of critical work, however, the Central American region and its literature have been largely ignored. This article, which focuses on the representation of lesbians and queer desire in the Guatemalan novel Labios (2004) ‘Lips’ by Maurice Echeverría, seeks to contribute to such a lack in Central American perspective. This essay contends, Echeverría’s text, one of a growing number of recent Central American narratives to call attention to and portray gay, lesbian, and/or transgender individuals and their experiences, evinces an alternate and composite form of visibility that can be understood as a visibilidad cosmo-queer. This visibility is an expression of the complex social reality of sexual minorities in postwar Guatemala, one marked by global or cosmopolitan discourses of gay and lesbian identity politics as well as queer modes of self-definition that challenge those same dominant discourses.
Keywords: Maurice Echeverría; lesbian; Guatemala; postwar; gay literary studies; queer studies; Latin American cultural studies; Labios; visibilidad cosmoqueer; sexual minorities; identity